2021
DOI: 10.2147/opth.s307020
|View full text |Cite
|
Sign up to set email alerts
|

Combined Intense Pulsed Light and Low-Level Light Therapy for the Treatment of Dry Eye: A Retrospective Before–After Study with One-Year Follow-Up

Abstract: Purpose: To assess the effectiveness of a combination of intense pulsed light and low-level light therapy (IPL/LLLT) for the treatment of dry eye. Study Design: Retrospective before-after single-center clinical study. Materials and Methods: Patients diagnosed with dry eye, refractory to conventional treatment, underwent four sessions of combined IPL/LLLT over 3 months. The Ocular Surface Disease Index (OSDI) questionnaire, non-invasive breakup time (NIBUT), tear film osmolarity and meniscus height were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…Similarly, a retrospective study by Pérez-Silguero et al 38 showed significant decrease of DED manifestations after four sessions of IPL+LLLT (0, 1, 4, and 12 weeks). As previously mentioned, the positive effects of IPL are observed after the first treatment session, peak between the last session and subsequent follow-up (usually 1–2 months after the last treatment session), and start to fade afterwards (in this series, at 6-month follow-up after baseline).…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, a retrospective study by Pérez-Silguero et al 38 showed significant decrease of DED manifestations after four sessions of IPL+LLLT (0, 1, 4, and 12 weeks). As previously mentioned, the positive effects of IPL are observed after the first treatment session, peak between the last session and subsequent follow-up (usually 1–2 months after the last treatment session), and start to fade afterwards (in this series, at 6-month follow-up after baseline).…”
Section: Discussionmentioning
confidence: 71%
“…24 Regarding LLL, there is no published article exploring this treatment alone in humans. There are three previous single arm studies using IPL combined with LLL [12][13][14] , showing improvement in symptoms and objective measures, similar to the effect of IPL alone. However, proper comparisons with other studies using IPL alone were not possible given the variable methodologies used.…”
Section: Discussionmentioning
confidence: 79%
“…Other studies with longer follow-up periods observed an effect up to 3-6 months after similar treatment protocols. 8,12,14,19 It remains unclear if LLL will affect the results in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies with longer follow-up periods observed an effect up to 3–6 months after similar treatment protocols. 8 , 12 , 14 , 19 It remains unclear if LLLT will affect the results in the long term.…”
Section: Discussionmentioning
confidence: 99%